SMART-C: developing a 'smart city' assessment system using cognitive mapping and the Choquet integral - Castanho, M.; Ferreira, F.; Carayannis, E.; Ferreira, J. (IEEE Transactions on Engineering Management, 2021)
Rapid urbanization, high city population growth rates, technological development, environmental impacts, and human wellbeing in urban areas have over the years become increasingly challenging concerns. These trends are related to the complex, multiple factors to be considered when evaluating “smart” cities, that is, municipalities that seek to improve residents’ quality of life by combining new technologies and environmentally sustainable practices. The above tendencies thus add to the myriad of indicators that need to be included in smart city assessments, whose intricacy hinders related decision-making processes. Based on the principles of multiple criteria decision analysis (MCDA), this study sought to integrate cognitive mapping and the Choquet integral to develop an assessment system that facilitates the evaluation of smart cities, which was named “SMART-C”. The research included a panel of experts on smart cities who identified the evaluation criteria and their respective interactions. The results of a real-life application of the assessment system developed in this study were validated both by the panel members and a representative of the Lisboa E-Nova non-profit association of the Lisbon City Council’s Environment and Energy Department. These experts confirmed that the proposed evaluation system facilitates making distinctions between cities according to how fully they develop “smartness”. The advantages and limitations of this assessment framework are also discussed.